Ayatollah Khomeini and the foundation of legitimacy of power and government - Goudarzi, Masoumeh Rad; Jawan, Jayum; Ahmad, Zaid (Canadian Academy of Oriental and Occidental Culture, 2009)
Ayatollah Khomeini, in contrary with pre-dominant trend of thought in Shi’a, announced establishment of Islamic government in the occultation era necessary and an obligation for jurists. He with invoke to a set of transmitting and intellectual reasons tried to justify his theory of “Governance of the Jurist” and granted to it a divine legitimacy, which is examined in the first part of the present research. But how he viewed the role of people in legitimizing of his acceptable type of government? Despite that he believed to divine legitimacy of Governance of the Jurists, but acceptance and satisfactory of people was also strongly emphasized by him. In second part of the present research, the researcher investigates how he combined between divine right of the jurists and popular right in legitimizing of power and government.